PENGEMBANGAN KETERAMPILAN REMAJA TENTANG TEKNIK RESUSITASI JANTUNG PARU MELALUI KEGIATAN PELATIHAN TEKNOLOGI INTERAKTIF (E-LEARNING DAN ROLE PLAY) - Tumilantouw, Dina Erika; Ake, Julianus; Wetik, Syenshie Virgini (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2024)
Introduction: Cardiac arrest is one of the main problems in the cardiovascular system which can be fatal and even cause death. Cardiopulmonary Resuscitation (CPR) is a fast and effective method for treating this condition, so it is important for people, especially teenagers, to understand and master this technique. Objective: This study aims to analyze the effect of e-learning and role play based CPR training on adolescent skills in Sion Village, Tompaso Baru District. Method: The research uses a quantitative approach with pre-experimental methods and One Group Pre-Test Post-Test research design. The research population consisted of 50 teenagers aged 13–19 years, with 15 respondents selected using purposive sampling techniques. Results: Based on non-parametric statistical tests using the Wilcoxon test with a P-Value 0.001. This shows that Ho is rejected and Ha is accepted, which means there is a significant influence on teenagers' skills before and after being given RJP training based on e-learning and role play. Conclusion: RJP training in the form of interactive technology (e-learning and role play) has had a significant impact on improving the skills of teenagers in Sion Village, Tompaso Baru District